Accuracy of Suction Rectal Biopsy for Diagnosis of Hirschsprung's Disease in Neonates - Allen, Ashley Rebekah; Putnam, Angelica R.; Presson, Angela P.; Allen, Chelsea McCarty; Barnhart, Douglas C.; Rollins, Michael D. (European Journal of Pediatric Surgery, 2019)
Introduction Recent publications have questioned the sensitivity of suction rectal biopsy (SRB) for diagnosis of Hirschsprung's disease (HD) in newborns. A recent European survey reported that 39% of pediatric surgeons performed full-thickness transanal biopsies due to concerns about the accuracy of SRB. We sought to examine our contemporary SRB experience in infants.Materials and Methods A review was performed (2007–2016) of patients under 6 months of age who had a SRB at our children's hospital. The cohort was subdivided by postmenstrual age at time of SRB: preterm (< 40 weeks, A), term neonate (40–44 weeks, B), and infant (> 44 weeks, C). The pathology reports from endorectal pull-through were used as gold standard confirmation. One-year follow-up of patients with negative SRB was used to confirm accurate diagnosis.Results A total of 153 patients met the criteria and a total of 159 SRBs (< 2,500 g; n = 26) were performed (A = 60, B = 58, C = 35). Forty-three patients were diagnosed with HD (A = 25, B = 15, C = 3). A second SRB was performed in 6 (3.9%) patients due to inadequate tissue (A = 2, B = 2, C = 2) with HD diagnosed in 5. No complications occurred. Sensitivity and specificity of SRB was 100% in all age groups. Half of the patients with a negative SRB had at least 1 year follow-up, with none subsequently diagnosed with HD.Conclusion SRB results in adequate tissue for evaluation of HD in nearly all patients less than 6 months of age on the first attempt and is highly accurate in the preterm and newborn infants. No complications occurred, even among infants less than 2,500 g.
Keywords: Hirschsprung's disease; rectal biopsy; suction rectal biopsy